2023
DOI: 10.1097/jcp.0000000000001630
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Safety of Trazodone After Maternal Exposure in Early Pregnancy

Abstract: Purpose/Background Trazodone is indicated for the treatment of major depressive disorder, but more frequently prescribed off-label at lower doses for insomnia in women of childbearing age. The aim of this study was to assess the risks linked to trazodone exposure during pregnancy for which limited safety data are available. Methods/Procedures This multicenter, observational prospective cohort study compared pregnancy outcomes in women exposed to trazodone in early pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…We also found 12 studies that evaluated malformation risk after exposure to multimodal antidepressants during pregnancy ( Table 5 ). Of these, the majority reported results not controlled for possible indication bias as follows: seven studies evaluated MM risk; one resulted in significant risk [ 85 ] while six resulted in non-significant MM risk [ 49 , 87 , 88 , 89 , 90 , 91 ]; five studies evaluated CM risk, one resulted in significant risk [ 64 ] while four resulted in non-significant CM risk [ 49 , 56 , 59 , 92 ]. After controlling for indication, or at least partially accounting for an underlying psychiatric condition, no study resulted in significant risk for MM, while two resulted in non-significant MM risk [ 85 , 93 ]; only one study reported significant CM risk [ 64 ] while three studies resulted in non-significant CM risk [ 56 , 59 , 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…We also found 12 studies that evaluated malformation risk after exposure to multimodal antidepressants during pregnancy ( Table 5 ). Of these, the majority reported results not controlled for possible indication bias as follows: seven studies evaluated MM risk; one resulted in significant risk [ 85 ] while six resulted in non-significant MM risk [ 49 , 87 , 88 , 89 , 90 , 91 ]; five studies evaluated CM risk, one resulted in significant risk [ 64 ] while four resulted in non-significant CM risk [ 49 , 56 , 59 , 92 ]. After controlling for indication, or at least partially accounting for an underlying psychiatric condition, no study resulted in significant risk for MM, while two resulted in non-significant MM risk [ 85 , 93 ]; only one study reported significant CM risk [ 64 ] while three studies resulted in non-significant CM risk [ 56 , 59 , 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…For this study, additional data pertaining to diabetes severity and obesity were also collected, where available. Socioeconomic and educational data were mostly not recorded 22…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, exclusion criteria encompassed exposure to angiotensin-converting enzyme inhibitors, angiotensin II receptor blockers or tetracyclines during the second and third trimesters, presence of malignancies or malignancy-related conditions, multiple pregnancies and duplicate cases. Data sent from different TIS were analysed anonymously 22…”
Section: Methodsmentioning
confidence: 99%
“…Animal data and available human pregnancy exposure data (based primarily on three studies involving 171 trazodone‐exposed patients during the first trimester) have provided suggestive evidence of the drug's safety when used in pregnancy, but the literature on this question remains limited. The purpose of this prospective study was to evaluate risks of trazodone exposure, including major congenital anomalies and other adverse pregnancy and neonatal outcomes, during the first trimester of pregnancy compared with reference exposure to the selective serotonin reuptake inhibitors (SSRIs) sertraline, citalopram, or escitalopram (Dao et al, 2023).…”
Section: Population Studymentioning
confidence: 99%